The potential of co-creation spaces to contribute to Sustainable Development - Iscenco, Alexandr (Ökologisches Wirtschaften - Fachzeitschrift, 2015)
Collaborative production in community-based open workshops has a potential to contribute to sustainable development. The article explores how open workshops, collaborative innovation and manufacturing can contribute to sustainability of a city such as Berlin.